FINANCIAL VIOLATIONS IN THE IMPLEMENTATION PUBLIC PROCUREMENT IN UKRAINE AND MEANS OF MINIMIZING THEM (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The article reveals the features of the manifestation of financial violations in the implementation of public procurement in Ukraine and their causes; the financial problems that exist in Ukraine during the tender procurement as well as the problems in the activities of the regulatory authorities of the country during the control of public procurement were studied. The directions of reforming the mechanism of financial control over the implementation of public procurement in Ukraine, taking into account the experience of the European Union were substantiated in the article; financial features of the implementation of public procurement after the entry into force of the new version of the Law of Ukraine "On Public Procurement" were detected; the forms of financial responsibility of participants and customers of public procurement in Ukraine as concerns of their effectiveness were studied; ways to increase their effectiveness were proposed.Public procurement has become the largest market in Ukraine so it is necessary to achieve maximum efficiency from their implementation minimizing the existing shortcomings. Among them experts single out the following: corruption, low professional level of customers, paying little attention to the financial capacity of borrowers, imperfect legal regulation of qualification selection of borrowers, the predominance of price criteria when choosing a winner, lengthy tender procedure, insufficient provision of office equipment and Internet to work with ProZorro system as well as the existence of financial violations by customers and participants in public procurement in Ukraine. It stipulates the necessity to strengthen the financial responsibility on the part of all tenderers as both customers and suppliers commit certain abuses during tenders.The main shortcomings of financial control in the field of public procurement in Ukraine include duplication of functions of the State Audit Service and the Accounting Chamber; lack of a clearly defined methodology for controlling public procurement; the predominance of the next type of control over the previous one; lack of a clear mechanism for cooperation between law enforcement and regulatory authorities in the field of public procurement, etc. Another problem in Ukraine is that public control in the field of public procurement is not widespread enough. The implementation of the measures proposed by the authors to correct these shortcomings will achieve to increase the efficiency of public procurement in Ukraine and strengthens the financial responsibility of their participants. One of the main ones should be the prevention of financial violations in public procurement in Ukraine.
Keywords: public finance, public procurement, financial violations, financial responsibility of tenderers, European Union, Poland, Ukraine